/ PERBANDINGAN PENGATURAN DAN PENERAPAN PENDIRIAN USAHA MIKRO KECIL MENENGAH DI NEGARA INDONESIA DAN KERAJAAN BRITANIA RAYA: / - Victor Alexander Sewu; Sri Bakti Yunari (Reformasi Hukum Trisakti, 2024)
This research discusses the comparison of the regulation and application of Micro, Small and Medium Enterprises (MSMEs) in the Republic of Indonesia and the United Kingdom as stipulated in Government Regulation No. 7 of 2021 and the Small Business, Enterprise and Employment Act (SBEE) 2015. The formulation of the problem is how the regulation of the establishment of MSMEs and its application in the requirements of MSME establishment procedures in Indonesia and the United Kingdom. This research uses normative juridical methods with descriptive research properties using secondary data which is analyzed qualitatively with deductive inference. The results of the study show that the two countries have the same focus on increasing economic growth through support for MSMEs and making it easier in terms of establishment and licensing including government support, and incentives. While the differences are illustrated in terms of establishment and licensing procedures, where in Indonesia the establishment procedure requirements have been carried out through the Online Single Submission (OSS) which is designed to accelerate the licensing and business establishment process. The conclusion is that there are similarities and differences between the two countries in terms of regulating the establishment of MSMEs